Cardiac Mortality Among 200 000 Five-Year Survivors of Cancer Diagnosed at 15 to 39 Years of Age: The Teenage and Young Adult Cancer Survivor Study. Issue 20 (15th November 2016) - Henson, Katherine E.; Reulen, Raoul C.; Winter, David L.; Bright, Chloe J.; Fidler, Miranda M.; Frobisher, Clare; Guha, Joyeeta; Wong, Kwok F.; Kelly, Julie; Edgar, Angela B.; McCabe, Martin G.; Whelan, Jeremy; et al.
Abstract : Background: Survivors of teenage and young adult cancer are acknowledged as understudied. Little is known about their long-term adverse health risks, particularly of cardiac disease that is increased in other cancer populations where cardiotoxic treatments have been used. Methods: The Teenage and Young Adult Cancer Survivor Study cohort comprises 200 945 5-year survivors of cancer diagnosed at 15 to 39 years of age in England and Wales from 1971 to 2006, and followed to 2014. Standardized mortality ratios, absolute excess risks, and cumulative risks were calculated. Results: Two thousand sixteen survivors died of cardiac disease. For all cancers combined, the standardized mortality ratios for all cardiac diseases combined was greatest for individuals diagnosed at 15 to 19 years of age (4.2; 95% confidence interval, 3.4–5.2) decreasing to 1.2 (95% confidence interval, 1.1–1.3) for individuals aged 35 to 39 years (2 P for trend <0.0001). Similar patterns were observed for both standardized mortality ratios and absolute excess risks for ischemic heart disease, valvular heart disease, and cardiomyopathy. Survivors of Hodgkin lymphoma, acute myeloid leukaemia, genitourinary cancers other than bladder cancer, non-Hodgkin lymphoma, lung cancer, leukaemia other than acute myeloid, central nervous system tumour, cervical cancer, and breast cancer experienced 3.8, 2.7, 2.0, 1.7, 1.7, 1.6, 1.4, 1.3 and 1.2 times the number of cardiac deaths expected from the general population, respectively. Among survivors of Hodgkin lymphoma aged over 60 years, almost 30% of the total excess number of deaths observed were due to heart disease. Conclusions: This study of over 200 000 cancer survivors shows that age at cancer diagnosis was critical in determining subsequent cardiac mortality risk. For the first time, risk estimates of cardiac death after each cancer diagnosed between the ages of 15 and 39 years have been derived from a large population-based cohort with prolonged follow-up. The evidence here provides an initial basis for developing evidence-based follow-up guidelines. Abstract : Supplemental Digital Content is available in the text.